STUDENT STRATEGIS TO OVERCAME PUBLIKSPEAKING ANXIETY : A CASE STUDY - Nia Nurhayati; Mohammad Soni; Rajji Koswara Adiredja (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Public speaking is an essential skill in foreign language learning at the university level. However, many students experience anxiety when they are required to speak or deliver presentations in front of an audience. This anxiety often hinders students’ classroom participation, reduces self-confidence, and negatively affects their speaking performance. This study aims to explore students’ experiences of public speaking anxiety, identify the factors contributing to it, and examine the strategies used by students to cope with this anxiety. This study employed a qualitative approach with a case study design. The participants consisted of ten university students who were purposively selected and actively enrolled in speaking courses. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that public speaking anxiety is commonly experienced by students and is mainly caused by limited vocabulary, fear of making grammatical and pronunciation errors, low self-confidence, and concern about negative evaluation from lecturers and peers. The anxiety affects students’ speaking performance, resulting in forgetting content, trembling voices, and loss of focus during speaking activities. To cope with anxiety, students employed various strategies, particularly thorough preparation and repeated practice before speaking, emotional regulation strategies, and the use of supportive learning environments. This study concludes that public speaking anxiety cannot be completely eliminated, but it can be effectively managed through appropriate strategies and supportive classroom conditions.